2013
DOI: 10.3758/s13415-013-0208-0
|View full text |Cite
|
Sign up to set email alerts
|

Grasping with the eyes: The role of elongation in visual recognition of manipulable objects

Abstract: Processing within the dorsal visual stream subserves object-directed action, whereas visual object recognition is mediated by the ventral visual stream. Recent findings suggest that the computations performed by the dorsal stream can nevertheless influence object recognition.Little is known, however, about the type of dorsal stream information that is available to assist in object recognition. Here we present a series of experiments that explored different psychophysical manipulations known to bias the process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
79
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(88 citation statements)
references
References 77 publications
6
79
3
Order By: Relevance
“…Our tools and nontools were matched for elongation, both absolute and familiar size, viewing distance, material properties, and graspability, and we nevertheless found higher activation for tools. While this does not rule out the possibility that tool processing is influenced by elongation (Sakuraba et al, 2012;Almeida et al, 2014) and real-world size of the object (Konkle & Oliva, 2012), our data show that these confounds cannot fully account for the differences in activation between tools and non-tools. Rather, the critical factor in tool-selective activation is the learned associations between a tool's structure and its function.…”
Section: Tools Vs Non-toolscontrasting
confidence: 54%
“…Our tools and nontools were matched for elongation, both absolute and familiar size, viewing distance, material properties, and graspability, and we nevertheless found higher activation for tools. While this does not rule out the possibility that tool processing is influenced by elongation (Sakuraba et al, 2012;Almeida et al, 2014) and real-world size of the object (Konkle & Oliva, 2012), our data show that these confounds cannot fully account for the differences in activation between tools and non-tools. Rather, the critical factor in tool-selective activation is the learned associations between a tool's structure and its function.…”
Section: Tools Vs Non-toolscontrasting
confidence: 54%
“…It may be hypothesized that in D.F.’s isolated dorsal stream, rotation of the wrist is only sensitive to one major visual axis at a time, rendering it limited to translating visual orientation into oriented action reliably only with stimuli where there is a single major axis. Recent psychophysical evidence supports this idea (Almeida et al 2014). If this is so, then a healthy person’s performance of these two more visually complex tasks may depend upon input from shape processing systems in the ventral stream that are able to upgrade such a first-order orientation visuomotor channel in the dorsal stream into a more flexible one that can simultaneously handle multiple visual axes.…”
Section: Evidence For Ventral-to-dorsal Trafficmentioning
confidence: 80%
“…3. Almeida et al (2013) found that recognition of elongated tools was primed both by elongated tools and elongated animals, but did not test whether non-elongated tools could be primed by elongated stimuli. Shape priming thus remains an alternative explanation for their results.…”
Section: Grasping Under Cfsmentioning
confidence: 85%
“…In a further study including both elongated and non-elongated tools as primes, it was argued that exactly the 'elongatedness' of the stimuli is the key factor deciding whether a stimulus is graspable and hence activates the dorsal stream, since non-elongated tools did not elicit the same priming effect (Almeida et al, 2013). But since the study included only elongated targets, it cannot conclusively argue against a shape-priming hypothesis (see Fig.…”
Section: Evidence From Priming Studiesmentioning
confidence: 98%